Surface roughness study of milled carbon fiber reinforced polymer (CFRP) composite using 4 mm 2-flute titanium aluminum nitride (TiAlN) coated carbide end mills - Konneh, Mohamed; Sudin, Izman; Padil, Mirza Emmil Dzahi; Roszat, Rosniza (Trans Tech Publications, Switzerland, 2014)
As the goal for aircraft weight reduction and low fuel consumption becomes a dire concern in aerospace industries, there is driving desire for the increasing use of advanced exotic materials such as composites, titanium and Inconels in the aerospace industry because of their high strength to weight ratio. Nevertheless the inherent anisotropy, inhomogeneous properties of CFRP and low bonding strength within the laminates make machining of these composite materials results in several undesirable effects such as delamination, micro-cracking, burr, fiber pull out and breakage. This paper discusses an experimental investigation into the influence of machining parameters on surface roughness when milling CFRP using 4 mm-diameter 2-fluted carbide endmill coated with Titanium Aluminium Nitride (TiAlN). Relationship between the machining variables and the output variables is established and a mathematical model is predicted for the surface roughness produced during the milling process for the machining conditions investigated.